Enhancing Financial Literacy, Digital Literacy, and Technology-Based Career Readiness among Students of SMK Perintis 1 Depok, West Java - Darmansyah Darmansyah; Hotman Fredy; Arissetyanto Nugroho; Irvandi Gustari; Ahmad Ramdani Salim; Winda Wulandari; Retna Sari; Wieldy Menanda (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Digital transformation has shifted the competency paradigm required by vocational education graduates. Vocational High School (SMK) students currently face a triple challenge: financial management amidst the rise of fintech, ethical use of technology, and digitalized career competition. This community service activity aims to enhance the understanding and skills of SMK Perintis 1 Depok students through an integrated educational intervention. The method employed is an educational-participatory approach through seminars, practical training, and simulations involving 100 students. The effectiveness evaluation was conducted using a Paired Sample T-Test analysis on pre-test and post-test scores. Results showed significant improvements: financial literacy (58 to 82), digital literacy (61 to 85), and career readiness (55 to 84). A p-value < 0.05 proves the real impact of the intervention. The discussion highlights that the synergy between digital and financial literacy serves as a foundation for student resilience in facing economic uncertainty in the digital economy era.